Decentralized identifiers based IoT data trusted collection - Baitao Zhang; Rui Shi; Xiaolin Li; Mengjiao Zhang (Scientific Reports)
Abstract The data collection processes of IoT devices face significant security challenges, including access authorization, secure transmission, and secure storage. These challenges are particularly critical in sectors such as smart healthcare, smart homes, and smart cities, where users often lack direct ownership or control over IoT devices. Various solutions have been proposed to address these issues, leveraging technologies such as Certificate Authorities (CAs) and blockchain. However, the CA model is inherently centralized, while blockchain-based solutions suffer from relatively low efficiency. To overcome these limitations, this article introduces a trust model for IoT data collection based on Decentralized Identifiers (DIDs) and proposes a novel IoT data security collection scheme, called TrID. TrID employs a distributed architecture to resolve the centralization problem and operates independently of blockchain, significantly enhancing both the security and efficiency of IoT data collection. The experiment shows that the authentication time cost of TrID in the mutual authentication protocol is only 10% of on-chain solutions, and the decryption of 10 MB of data with 1000 KB encrypted block size, requires less than 100 ms.